2020
DOI: 10.1111/plb.13139
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic regulation of polyamines and γ‐aminobutyric acid in relation to spermidine‐induced heat tolerance in white clover

Abstract: • Heat stress decreases crop growth and yield worldwide. Spermidine (Spd) is a small aliphatic amine and acts as a ubiquitous regulator for plant growth, development and stress tolerance. • Objectives of this study were to determine effects of exogenous Spd on changes in endogenous polyamine (PA) and c-aminobutyric acid (GABA) metabolism, oxidative damage, senescence and heat shock protein (HSP) expression in white clover subjected to heat stress. Physiological and molecular methods, including colorimetric ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 57 publications
(56 reference statements)
3
13
0
Order By: Relevance
“…An previous study in creeping bentgrass has shown that the GABA exhibited positive function in alleviating heat-induced chlorophyll loss and photoinhibition [ 13 ]. The recent study also found that enhanced GABA accumulation and metabolism helped to maintain chlorophyll synthesis and decrease chlorophyll degradation in white clover, thereby mitigating the decline in photosynthesis during heat stress [ 12 ]. In current study, the creeping bentgrass with GABA priming maintained better photochemical efficiency (Fv/Fm), photosynthetic performance (PIABS), cell membrane stability, and OA than untreated plants in response to a prolonged period of heat stress, indicating that the beneficial function of GABA on alleviating heat damage could be associated with better photoprotective response and water regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An previous study in creeping bentgrass has shown that the GABA exhibited positive function in alleviating heat-induced chlorophyll loss and photoinhibition [ 13 ]. The recent study also found that enhanced GABA accumulation and metabolism helped to maintain chlorophyll synthesis and decrease chlorophyll degradation in white clover, thereby mitigating the decline in photosynthesis during heat stress [ 12 ]. In current study, the creeping bentgrass with GABA priming maintained better photochemical efficiency (Fv/Fm), photosynthetic performance (PIABS), cell membrane stability, and OA than untreated plants in response to a prolonged period of heat stress, indicating that the beneficial function of GABA on alleviating heat damage could be associated with better photoprotective response and water regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant capacity and water balance regulated by exogenous GABA helped rice ( Oryza sativa ) seedlings to acclimate heat stress [ 11 ]. Enhanced GABA accumulation and metabolism contributed to the alleviation of heat-induced leaf senescence associated with significant increase in chlorophyll synthesis in white clover ( Trifolium repens ) [ 12 ]. Previous studies also found that foliar application of GABA significantly improved the thermotolerance of creeping bentgrass ( Agrostis stolonifera ) in relation to organic metabolites accumulation and upregulation of genes encoding antioxidant enzymes, stress-defensive proteins, and transcription factors [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polyamines (PA), including putrescine (Put), spermidine (Spd), and spermine (Spm), are a class of significant physiologically active substances in plants, involved in plant growth and development and response to various abiotic stresses, among which Spd is closely related to seed development and plant heat tolerance [7][8][9][10][11]. Soaking seeds in Spd significantly enhanced seed vigor, while exogenous cyclohexylamine (CHA), a Spd synthesis inhibitor, significantly inhibited seed germination and reduced seed vigor [12].…”
Section: Introductionmentioning
confidence: 99%
“…The Fv/Fm reflects the main photochemical efficiency of PSII and PIABS synthetically indicates the maximum photochemical efficiency of PSII, with the total number of activated reactive centers functioning as a sensitive photosynthetic indicator of photosynthetic performance, as well as for the health status of photosynthetic organs in plants under abiotic stress [ 28 , 29 ]. Some studies have shown that heat stress leads to a significant decrease in the Fv/Fm and PIABS of wheat, white clover, and creeping bentgrass [ 3 , 30 , 31 ]. Our results showed that Fv/Fm and PIABS decreased significantly under heat stress in the leaves of creeping bentgrass, and that exogenous CTS could mitigate the adverse effect of heat stress on the Fv/Fm and PIABS of creeping bentgrass.…”
Section: Discussionmentioning
confidence: 99%
“…This could be related to the fact that CTS has been proven to significantly increase AsPBGD expression, as well as effectively alleviate heat-induced declines in AsCHLH expression while increasing the AsPPH transcript levels. Our previous studies found that mannose-regulated leaf senescence was not correlated with PBGD expression in white clover under water stress [ 39 ], but spermidine significantly up-regulated the PBGD expression, contributing to less Chl degradation occurring in the leaves of white clover during heat stress [ 31 ]. These findings indicate that different exogenous additives cause different effects on Chl metabolism.…”
Section: Discussionmentioning
confidence: 99%